Risk factors of stroke - Bhatt, VR; Parajuli, N; Mainali, NR; Sigdel, S; Aryal, M; Hamal, N; Khanal, S; Koirala, S; Giri, S (Journal of Institute of Medicine Nepal, 2009)
Background: Modifiable risk factors of stroke are presumably poorly controlled in Nepalese population. This hospital-based study aims to assess the prevalence and control of these risk factors in stroke patients admitted to Tribhuvan University Teaching Hospital prior to the occurrence of stroke. Method: The study was conducted among sixty-one patients admitted in Tribhuvan University Teaching Hospital. History and clinical examination were performed to gather relevant information. Necessary tests were run to confirm the diagnosis of stroke and to identify the presence or absence of risk factors. Result: Hypertension, physical inactivity and smoking were the most common modifiable risk factors of stroke. Risk factors that could have contributed to the occurrence of the stroke were poorly controlled in these patients. The majority of the patients cited negligence and lack of knowledge for not seeking health care and/or not complying with medical advice. Conclusion: Risk factors for stroke among patients admitted to Tribhuvan University Teaching Hospital are poorly controlled prior to the occurrence of stroke. Key words: Stroke, Hypertension, Smoking The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 37-41